2017
DOI: 10.1098/rsbl.2016.0743
|View full text |Cite
|
Sign up to set email alerts
|

Ant circadian activity associated with brood care type

Abstract: In group-living animals, social interactions influence various traits including circadian activity. Maternal care, in particular, can have a strong effect on the circadian activity of parents or nurses across taxa. In social insects, nestmates are known to have diverse activity rhythms; however, what kind of social environment is crucial in shaping an individual's rhythm is largely unknown. Here, we show that the focal brood types being taken care of (i.e. egg, larva and pupa) have significant effects on indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 26 publications
3
60
0
Order By: Relevance
“…A possible explanation put forward was that larvae need care around-theclock, whereas foraging efficiency varies depending on the time of the day. This hypothesis was supported by the finding that experimental addition of brood to rhythmic individuals dramatically decreases the strength of their rhythm in Diacamma ants (Fujioka et al, 2017; but see Fuchikawa et al, 2014), bumblebees (Eban-Rothschild et al, 2011), and honeybees (Shemesh et al, 2010). One specificity of our study is that we recorded any type of activity inside the nest that was not limited to nursing behavior.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…A possible explanation put forward was that larvae need care around-theclock, whereas foraging efficiency varies depending on the time of the day. This hypothesis was supported by the finding that experimental addition of brood to rhythmic individuals dramatically decreases the strength of their rhythm in Diacamma ants (Fujioka et al, 2017; but see Fuchikawa et al, 2014), bumblebees (Eban-Rothschild et al, 2011), and honeybees (Shemesh et al, 2010). One specificity of our study is that we recorded any type of activity inside the nest that was not limited to nursing behavior.…”
Section: Discussionsupporting
confidence: 61%
“…This situation is not unnatural for Temnothorax ants (Foitzik et al, 2004), as they inhabit small ephemeral nest sites such as acorns, where light shines in through the nest entrance. In addition, previous studies that reported an absence of rhythm for ant nurse workers also provided them with access to light (Fujioka et al, 2017;Mildner and Roces, 2017;Sharma et al, 2004). However, bee nurses show stronger synchronization when exposed to a light:dark regime (Fuchikawa et al, 2016;Shemesh et al, 2007Shemesh et al, , 2010, which could facilitate the detection of group-level rhythmicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, honey bee foragers are active during the daytime, namely flowering time, so that they can collect nectar and pollen (Bloch, Bar-Shai, Cytter, & Green, 2017). In contrast, nurse ants and bees are active all day long inside the nests because around-the-clock, brood care is considered necessary (Fujioka et al, 2017;Moore, Angel, Cheeseman, Fahrbach, & Robinson, 1998). In contrast, nurse ants and bees are active all day long inside the nests because around-the-clock, brood care is considered necessary (Fujioka et al, 2017;Moore, Angel, Cheeseman, Fahrbach, & Robinson, 1998).…”
mentioning
confidence: 99%
“…Likewise, ant foragers exhibit circadian activity rhythms, that is, they have a periodic activity of approximately 24 hr: some species are diurnal and others are nocturnal (Lewis, Pollard, & Dibley, 1974;. In contrast, nurse ants and bees are active all day long inside the nests because around-the-clock, brood care is considered necessary (Fujioka et al, 2017;Moore, Angel, Cheeseman, Fahrbach, & Robinson, 1998). Thus, the time schedules of tasks are expected to depend on characteristics of the tasks.…”
mentioning
confidence: 99%